Data for "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada" ... - Wang, Bo; Kyzivat, Ethan (Zenodo, 2023)
Water surface elevation, river depth, and ADCP data for the WRR paper "Athabasca River avulsion underway in the Peace-Athabasca Delta, Canada, Water Resources Research , Wang et al. 2023, in review". ...